Notes on Social Measurement : Historical and Critical - Duncan, Otis Dudley (Book collections on Project MUSE., 1984)
Social measurement, like physical measurement, is a persistent theme in human history. In this essay, an eminent sociologist suggests that social measurement has its roots in the social process itself, broadly conceived, and not specifically in the scientific method as it developed in the seventeenth and later centuries.